THE COOPERATIVE SCRIPT LEARNING MODEL ON THE ABILITY TO UNDERSTAND MATHEMATICAL CONCEPTS - Laowo, Nasowaauri; Sudung Kristopel Naiborhu; Fresty Handayani Togatorop; Purnama Raya Anjelina Situmorang; Vinita M L Gaol; Firman Pangaribuan; Hardi Tambunan (Universitas Nias Raya, 2025)
This study aims to determine the effect of the Cooperative Script learning model on students' mathematical concept comprehension skills. This research uses a quantitative approach with a quasi-experimental method and a pretest-posttest control group design. The population of this study is all 8th-grade students of SMP Negeri 1 Toma, and the research samples consist of class VIII-C as the experimental group and class VIII-D as the control group. The data were analyzed using the Liliefors test to check for normality, variance tests for homogeneity, and t-tests to test the hypothesis. The research findings show that: (1) the use of the Cooperative Script learning model improves students' ability to understand mathematical concepts and makes them more focused and actively engaged in learning; (2) the hypothesis test results show that tₕᵢₜ > tₜₐbᵗ (2.583 > 2.000), which leads to the rejection of the null hypothesis (Hₒ) and the acceptance of the alternative hypothesis (Hₐ). Therefore, it can be concluded that the Cooperative Script learning model influences students' mathematical concept comprehension abilities.